RETRACTED: Kajian Pelaksanaan Program Kewirausahaan Di Sekolah Insan Al Madani Bogor - Muhamad Agung Ali Fikri (LPPM Universitas Dharma Andalas, 2022)
This study aims to examine the strategy and evaluation of the entrepreneurship program at the Insan Al Madani school in Bogor and analyze the strengths, weaknesses, opportunities and threats. The research method was analyzed descriptively qualitatively through observation, SWOT analysis and literature study. Research data obtained from interviews with students, teachers and school principals, as well as several journal articles and research results that are relevant to the research theme. The results showed that the school held an entrepreneurship education program to foster an entrepreneurial spirit for students. Students are made in groups to produce a product, generally food and beverages, to be sold in the school environment to students, teachers and the surrounding community who are interested in buying these products. Internalizing the values ​​of entrepreneurship education with school subjects is an effort to increase students' soft skills and character. The entrepreneurship program is carried out periodically every academic year.